A Critical Study on Accounting Disclosure and Reporting Practices of Financial Derivatives in India - Pritinanda Sahoo; Dr. Prafulla Kumar Swain; Dr. Rabinarayan Patnaik (The Bioscan, 2025)
Purpose: This study aims to analyze the accounting disclosure practices of financial derivatives in India and further, the way firm size, profitability, and audit committee characteristics affect the quality of these disclosures. This includes an investigation of the direction between company attributes and reporting practices of financial derivatives. Design/Methodology/Approach: The study used a quantitative research design that integrated primary data gathered from a standardized questionnaire with secondary data sources. The sampling technique utilized here is purposive sampling and the sample size for 385 respondents has been calculated using Cochran’s formula. This study has used tools like SPSS 26 and Excel by applying various statistical techniques like Mean, Standard deviation, T-test, and ANOVA tools for the analysis of data. Findings: The findings of the research suggest that larger and more profitable firms are associated with better quality of disclosure of their derivative instruments, and also the companies with an active audit committee. On the other hand, other elements placed within the binding regulatory structures and the internal organizational culture of disclosers aimed at increasing the level of transparency of the process tend to obstruct the situation, hence, there is a need to obtain practical evidence regarding the practices of disclosure. Strategic considerations rather than compliance with rules govern the practice of disclosure. Pragmatic Outcomes: This study illustrates a gap that organizations in practice ought to start addressing which is to provide insight into the alignment in governance structure, particularly the make-up of audit committees as a way of accounting for financial derivatives. Understanding what type of characteristics of firms also affect disclosure practice will assist in looking for improved ways of boosting investor confidence and a move toward compliance. Originality/Value: This study fills an existing gap in the available literature by specifically focusing on firm size, profitability, and audit committee characteristics and their impact on financial derivatives disclosure in the Indian context. Thus, this study provides valuable input and insights to policymakers, corporate executives, and scholars about the validity of governance mechanisms as determinants in enhancing the quality of financial reporting.